Changes in rocky intertidal communities after the 2015 and 2017 El Niño events along the Peruvian coast. (5th March 2021) - Valqui, Juan; Ibañez-Erquiaga, Bruno; Pacheco, Aldo S.; Wilbur, Lynn; Ochoa, Diana; Cardich, Jorge; Pérez-Huaranga, Maria; Salas-Gismondi, Rodolfo; Pérez, Alexander; Indacochea, Aldo; Avila-Peltroche, Jose; Ch, Maria Rivera; et al.
Abstract: The Peruvian coast experiences the largest interannual variability of sea surface temperature in the world due to the combined influence of the coastal upwelling and El Niño Southern Oscillation (ENSO). Although biological impacts of El Niño events have been widely reported, their effects on rocky intertidal communities remains largely unknown in Peru. Herein, we analyze the results of two biological surveys of rocky intertidal communities, conducted along 1400 km of the Peruvian coast. The first survey was conducted in 2015 yielding a snapshot of the distribution of rocky intertidal communities after 17 years of stable La Niña-like conditions. The second survey was carried in October 2017, after the 2015-16 and the 2017 El Niño events, which produced warm sea surface temperature (SST) anomalies up to 6 °C on the Peruvian coast. We find no changes throughout the latitudinal transect in taxonomic richness but an important turnover of species, especially marked in the transition zone (~4–8°S) between the Panamic and the Humboldt provinces. Temperature-related southward migration of species was evidenced in a few sites but did not explain the large-scale change in communities observed from 2015 to 2017, primarily driven by large changes in the distribution of a few ecologically important species across the Panamic and Humboldt provinces. A primary environmental impact on some ecologically key species likely triggered a chain of secondary impacts through ecological relationships which lead to a complex change independent from SST gradients. Further studies are needed to better characterize and disentangle the seasonal and interannual variability of the rocky intertidal communities and their drivers. When this interannual variability is integrated, the nine study sites show a highly persistent community structure determined by the latitudinal SST gradient along the Peruvian coast. Graphical abstract: Image 1 Highlights: Rocky intertidal communities' response to El Niño in a latitudinal transect. Community changes driven by ecological processes rather than thermal tolerance. Biogeographical patterns are persistent to El Niño.